2008
DOI: 10.1158/1055-9965.epi-07-2830
|View full text |Cite
|
Sign up to set email alerts
|

Pathway Analysis of Single-Nucleotide Polymorphisms Potentially Associated with Glioblastoma Multiforme Susceptibility Using Random Forests

Abstract: Glioma is a complex disease that is unlikely to result from the effect of a single gene. Genetic analysis at the pathway level involving multiple genes may be more likely to capture gene-disease associations than analyzing genes one at a time. The current pilot study included 112 Caucasians with glioblastoma multiforme and 112 Caucasian healthy controls frequency matched to cases by age and gender. Subjects were genotyped using a commercially available (ParAllele/Affymetrix) assay panel of 10,177 nonsynonymous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
66
0
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 74 publications
(68 citation statements)
references
References 29 publications
1
66
0
1
Order By: Relevance
“…To date, a few molecular epidemiological studies have investigated the association between the EXO1 Glu589Lys polymorphism and the cancer risk including lung cancer (Zienolddiny et al, 2006;Jin et al, 2008;Hsu et al, 2008), glioma (Chang et al, 2008), breast cancer , gastric cancer (Bau et al, 2009), oral cancer , melanoma (Ibarrola-Villava et al, 2011), cervical (Luo et al, 2012), hepatocellular cancer (Bayram et al, 2012). However, no consistent conclusion has been drawn.…”
Section: Research Articlementioning
confidence: 99%
See 2 more Smart Citations
“…To date, a few molecular epidemiological studies have investigated the association between the EXO1 Glu589Lys polymorphism and the cancer risk including lung cancer (Zienolddiny et al, 2006;Jin et al, 2008;Hsu et al, 2008), glioma (Chang et al, 2008), breast cancer , gastric cancer (Bau et al, 2009), oral cancer , melanoma (Ibarrola-Villava et al, 2011), cervical (Luo et al, 2012), hepatocellular cancer (Bayram et al, 2012). However, no consistent conclusion has been drawn.…”
Section: Research Articlementioning
confidence: 99%
“…The study selection process is shown in Figure 1. A total of 10 case-control studies including 4391 cases and 4339 controls were analyzed in this metaanalysis (Zienolddiny et al, 2006;Chang et al, 2008;Hsu et al, 2008;Jin et al, 2008;Wang et al, 2009;Bau et al, 2009;Tsai et al, 2009;Ibarrola-Villava et al, 2011;Luo et al, 2012;Bayram et al, 2012). The characteristics of Exonuclease 1 Glu589Lys Gene Polymorphism and Cancer Susceptibility: Evidence Based on a Meta-Analysis selected studies are summarized in Table 1.…”
Section: Characteristics Of Eligible Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…We have listed about 20 epidemiological studies reporting positive associations between DNA repair polymorphisms and cancer risk (Table 1 [29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44][45] ). Only a small proportion of studies were large (five studies were more than 500 pair cases and controls) and population based; however, some consistencies in results are apparent.…”
Section: Pbts Molecular Epidemiologic Studies With Focus On Dna Repairmentioning
confidence: 99%
“…[9][10][11] Overall, random forests is among the best approaches for analyzing survival time using gene expression data. [12][13][14] In this article, we introduce one of the first methods to correlate SNP with survival outcomes.…”
Section: Introductionmentioning
confidence: 99%